Pathogene Corynebakterien: erfolgreiche Kolonisierer von Mensch und Tier - Ott, Lisa; Burkovski, Andreas (BioSpektrum, 2023)
The interaction of Corynebacterium diphtheriae and closely related species with host cells is much more complex than originally thought when these bacteria were considered as extracellular pathogens. Host-pathogen interaction studies revealed a wide range of virulence factors contributing to adhesion, invasion, and host cell damage to varying degrees. In combination, these factors lead to the successful colonization of host systems.
CRIS-Team Scopus Importer:2023-05-12